Laparoscopic and Robotic Total Mesorectal Excision in the Treatment of Rectal Cancer. Brief Review and Personal Remarks - Bianchi, Paolo Pietro; Petz, Wanda; Luca, Fabrizio; Biffi, Roberto; Spinoglio, Giuseppe; Montorsi, Marco (Frontiers in Oncology, 2014)
The current standard treatment for rectal cancer is based on a multimodality approach with preoperative radiochemotherapy in advanced cases and complete surgical removal through total mesorectal excision (TME). The most frequent surgical approach is traditional open surgery, as laparoscopic TME requires high technical skill, a long learning curve and is not widespread, still being confined to centres with great experience in minimally-invasive techniques. Nevertheless, in several studies, the laparoscopic approach, when compared to open surgery, has shown some better short-term clinical outcomes and at least comparable oncologic results. Robotic surgery for the treatment of rectal cancer is an emerging technique which could overcome some of the technical difficulties posed by standard laparoscopy, but evidence from the literature regarding its oncologic safety and clinical outcomes is still lacking. This brief review analyses the current status of minimally-invasive surgery for rectal cancer therapy, focusing on oncologic safety and the new robotic approach.